Character Education Management In The Development of Student Morality - Muchtarom, Muchtarom (The International Journal of Education Management and Sociology, 2023)
This study aims to determine the description of planning, organizing, actuating, and controlling character education in the development of student morals in Madrasah Aliyah al-Najah and Madrasah Aliyah al-Falah Jakarta. The theory used in this research was a qualitative approach. Data collection was done using observation, interview, and documentation studies. The results showed that: First, Madrasah Aliyah carried out planning by creating a vision, mission, environmental analysis, and curriculum. Second, organizing was done by creating organizational structures for foundations and schools. Third, actuating was done by associating character education with all subjects and practicing education management in the teaching and learning process. Fourth, Controlling was carried out by conducting evaluations, both formal and non-formal evaluations. Formal evaluation was carried out by conducting UTS (Midterm Examination) and UAS (Final Semester Examination). Meanwhile, non-formal evaluations were to find out the cognitive, affective, and psychomotor aspects of the learners.